Development and validation of a Comprehensive Level-Based Framework for Neurogenic communication disorders (CLFN). - Subudhi, Nikita M; Anil, Malavika Anakkathil; Mohan, Megha; Bhat, Jayashree S (NeuroRehabilitation, 2024)
Background: Acquired neurogenic communication disorders are neurological disorders' most commonly observed consequences. Profiling communication characteristics are a sensitive indicator in the tertiary centre that helps individualised management strategy to improve the quality of life in individuals with neurogenic communication disorders. Objective: The research aimed to develop and validate a Comprehensive Level-based Framework for Neurogenic communication disorders (CLFN) by profiling the communication characteristics of individuals with acquired neurogenic communication disorders in a tertiary care centre. Methods: The research followed a cross-sectional design and used a convenient sampling process for sample collection. A total of 76 participants were recruited for the research based on selection criteria. The initial administration of CLFN was documented as pre-levels for each domain for all the participants. A re-administration of CLFN was performed after 10 sessions over 7 days of intervention which was documented as post-levels. Results: A greater proportion of participants were from the middle-aged group than in the older age group, and males were observed to have a higher frequency occurrence of neurogenic communication disorders than females. Pairwise comparison between pre-levels and post-levels was statistically significant for speech intelligibility, cognitive-communication orientation, cognitive-communication memory, cognitive-communication executive function, communication, spoken language expression, spoken language comprehension, repetition, naming, and writing domains. Conclusions: The CLFN for Neurogenic communication disorders can serve as a reference for the holistic assessment of individuals with neurogenic communication disorders in a tertiary care centre. This will monitor the progress evaluation and plan the intervention program before the manifestation of any significant neurogenic impairment, which would improve individuals' quality of life.